Scientific Ideas Included in the Concepts of Bioacoustics, Acoustic Ecology, Ecoacoustics, Soundscape Ecology, and Vibroacoustics - Agnieszka OZGA (Archives of Acoustics, 2017)
The paper discusses the research areas which are placed in the modern science on the borderline between ecology and acoustics. It is explained what ideas are included in the concepts of bioacoustics, acoustic ecology, ecoacoustics, and soundscape ecology. The results obtained in these domains are compared with those received in vibroacoustic research presented at the Polish WIBROTECH conference cycle. The paper suggests an inventory of research topics connected with acoustics and ecology. In the second part of the paper the author presents the possibilities of ambisonic technology of recording and listening to sounds for the analysis in bioacoustic research.